Relational Risk and Collective Management: A Pathway to Transformational Risk Management. Issue 10 (31st January 2021) - Kamstra, Peter; Cook, Brian; Edensor, Tim; Kennedy, David; Kearnes, Matthew
Abstract: Risk tends to be conceptualized at the individual scale, with global risk communication and governance efforts fixated on an individual's knowledge and behavior. While individuals are undoubtedly influenced by those who surround them, such human–human interactions tend to be excluded from empirical and field‐based analyses of risk taking. This study diverges from prevailing analyses of risk as an individualized phenomenon, exploring the collective and relational practices that influence risk while fishing from hazardous rocky coasts. The aim is to counter the near‐universal tendency to individualize risk in empirical analyses by instead using a mixed‐methodology that can quantify and enable consideration of collective responses to risk, in real‐time. We demonstrate that both rock fishing practice and many of the high‐risk events that emerge while rock fishing are managed collectively. Compared to the tendency to individualize risk, we demonstrate that collective responses to risk are more representative of how risk is experienced and acted upon, with implications for risk management in countless contexts.